2014
DOI: 10.1155/2014/426785
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Glass and Printable Flexible Dye-Sensitized Solar Cells with Water-Based Electrolytes

Abstract: The performance of a flexible and glass dye-sensitized solar cell (DSSC) with water-based electrolyte solutions is described. High concentrations of alkylamidazoliums were used to overcome the deleterious effect of water and, based on this variable, pure water-based electrolyte DSSCs were tested displaying the highest recorded efficiency so far of 3.45% and 6% for flexible and glass cells, respectively, under a simulated air mass 1.5 solar spectrum illumination at 100 mWcm−2. An improvement in the Jsc with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A cell with a binary IL of 1-ethyl-3-methylimidazolium tetracyanoborate in combination with PMII showed a stable efficiency of 7% that retained at least 90% of its initial efficiency after 1000 h at 80 °C in darkness and 1000 h at 60 °C, at AM 1.5 [ 117 ]. Moudam et al studied the effect of water-based electrolytes in DSSC and demonstrated a highly efficient glass and printable flexible dye-sensitized solar cells upon application [ 118 ]. They used high concentrations of alkylamidazoliums to overcome the deleterious effect of water.…”
Section: Previous and Further Improvements In Dsscsmentioning
confidence: 99%
“…A cell with a binary IL of 1-ethyl-3-methylimidazolium tetracyanoborate in combination with PMII showed a stable efficiency of 7% that retained at least 90% of its initial efficiency after 1000 h at 80 °C in darkness and 1000 h at 60 °C, at AM 1.5 [ 117 ]. Moudam et al studied the effect of water-based electrolytes in DSSC and demonstrated a highly efficient glass and printable flexible dye-sensitized solar cells upon application [ 118 ]. They used high concentrations of alkylamidazoliums to overcome the deleterious effect of water.…”
Section: Previous and Further Improvements In Dsscsmentioning
confidence: 99%